Postoperative Bronchopleural Fistula - Murat, Ayşe; Balcı, Akın Eraslan; Ersoy, Ferda; Çetinkaya, Şeblem (Fırat University, 2004)
Bronchopleural fistula (BPF) remains the most dreaded complication following thoracic surgery. Its prevalence is reported to range between 0.8% and 15%. Mortality rates for BPF range from 30% to 70%. BPF commonly occurs after right pneumonectomy. Predisposing factors are preoperative uncontrolled pleuropulmonary infection, trauma, and preoperative radiation therapy. CT findings in BPF include air and fluid collections in the pleural space and demonstration of a communication or tract from an airway or the lung parenchyma to the pleural space. A 65 year-old male patient was admitted to our hospital with purulent sputum production and cough. In his history, right bilobectomy and complementary pneumonectomy was performed due to right lung mass. 6 months after the latter surgical operation, his complaints occurred. We present clinical and radiological findings of the patient which diagnosed as BPF, clinically. ©2004, Fırat Üniversitesi, Tıp Fakültesi

Bronkoplevral fistül (BPF), torasik cerrahi sonrası gelişebilecek en kötü komplikasyondur. Bildirilen sıklığı, % 0,8-15'dir. Mortalite oranı ise % 30- 70'dir. BPF, çoğunlukla sağ pnömonektomiden sonra görülür. Preoperatif kontrol edilemeyen plevropulmoner enfeksiyon, travma ve preoperatif radyoterapi uygulanması predispozan faktörlerdir. BPF'deki BT bulguları plevral alandaki hava-sıvı koleksiyonunu içerir ve hava yolundan veya akciğer parankiminden plevral alana olan fistül traktını veya ilişkiyi gösterir. Sağ akciğerindeki kitle nedeniyle, sağ bilobektomi ve tamamlayıcı pnömonektomi uygulanan 65 yaşındaki erkek hastada, ikinci operasyondan 6 ay sonra, pürülan balgam çıkarma ve öksürük şikayetleri başlamış. Klinik olarak BPF tanısı konulan hastanın klinik ve radyolojik bulgularını sunuyoruz. ©2004, Fırat Üniversitesi, Tıp Fakültesi
Postoperatif Gelişen Bronkoplevral Fistül